The Social Construction of Tolerance Discourse through Online Media: Study of NU Online - Suluh Gembyeng Ciptadi (Fakultas Dakwah UIN Saizu Purwokerto, 2024)
As the largest Islamic organization in Indonesia, Nahdlatul Ulama (NU) plays a major role in maintaining the country's diversity. As we know, intolerance among Indonesians has become a major problem for the nation. This research examines how NU constructs and spreads the value of tolerance through its online media, called “NU Online.” The theory of the social construction of reality, written by Berger and Luckmann, is used as a theoretical framework to depict internalization, objectification, and externalization processes in NU Online while constructing and spreading tolerance issues. Data were collected using a qualitative method, interviewing NU Online's members and editorial teams. The results of this study show that NU has an organizational value that regards tolerance as an important aspect of religious life. Moreover, the Islamic value of NU became a behavioral basis for all NU members, including members of NU Online. This value is called Ahlusunnah Waljamaah. Since becoming NU members, they have been internalized by the Ahlusunnah Waljamaah as a core value of the organization. Furthermore, in NU Online, this value spreads to the public through objectification and externalization processes.